2020
DOI: 10.21203/rs.3.rs-24107/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Ultrasound-assisted and Pure Fluoroscopy-guided Extracorporeal Shockwave Lithotripsy for Renal Stones

Abstract: Background: In this study, we aimed to compare the efficacy and clinical outcomes of shock wave lithotripsy (SWL) for patients with renal stones using pure fluoroscopy (FS) or ultrasound-assisted (USa) localization with two lithotripters.Methods: We retrospectively identified 425 patients with renal calculi who underwent SWL with either a LiteMed LM-9200 ELMA lithotripter (209 cases), which combined ultrasound and fluoroscopic stone targeting or a Medispec EM-1000 lithotripter machine (216 cases), which used f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Fourth, there were differences in stone composition, such as stone density (ranged between 600-1,000 Hounsfield units [HU], except for four studies that did not include stone density data) and stone type (mentioned in two studies). 3,7,8,[12][13][14] Chang et al 4 found that using USG combined with fluoroscopy resulted in a much better SFR, with lower rates of re-treatment and complications. However, it should be noted that several factors have not been assessed in this study, such as stone composition, computed tomography (CT) values, and skin-to-stone distance, which may affect the final result.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourth, there were differences in stone composition, such as stone density (ranged between 600-1,000 Hounsfield units [HU], except for four studies that did not include stone density data) and stone type (mentioned in two studies). 3,7,8,[12][13][14] Chang et al 4 found that using USG combined with fluoroscopy resulted in a much better SFR, with lower rates of re-treatment and complications. However, it should be noted that several factors have not been assessed in this study, such as stone composition, computed tomography (CT) values, and skin-to-stone distance, which may affect the final result.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that several factors have not been assessed in this study, such as stone composition, computed tomography (CT) values, and skin-to-stone distance, which may affect the final result. 4 Abid et al 17 also conducted a study comparing the addition of USG to fluoroscopy with fluoroscopy alone to assess the reduction in the duration of fluoroscopy on ESWL. From a comparison of 40 total samples of adults with kidney stones, adding USG to fluoroscopy could significantly reduce the fluoroscopic time (p<0.0001), indirectly reducing the amount of radiation exposure in the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations